PERNICIOUS SYNDROME OF FALCIPARUM MALARIA AND LEUKAEMOID REACTION - Khan, Abdul Salam; Khan, Abdur Rahim; Rehman, Saifur (Journal of Ayub Medical College Abbottabad, 1988)
A female child aged 11 years, was referred to our Clinical Laboratory by private local medical specialist. The patient had 10 days history of fever of sudden onset. She had been given injection Amoxycillin and Injection Chloroquine by a general practioner. On examination the child was very sick and pale. The pulse was 140 beats/min, regular, temperature 100°F in axilla, systolic murmur was audible in a wide area over the praecordium. The liver palbable 3 fingers below the right subcostal margin. X-ray chest showed mitralization and shifting of right border of the heart (fluid overload). Lung fields were congested. Hematological findings were Hb 7.0 gm/dl ESR, 95mm in 1st hour, TLC, 55,500/m3 and DLC, Neutrophils 83%, Metamyelocytes 4%, Myelocytes 02%, Band forms 04% and Lymphocytes 2%. The Neutrophils showed toxic granulations. The reticulocyte, count was not done as the patient expired. Normoblasts were 5%. Both basophilic and polychromatic forms were seen. The blood film was positive for malaria. The slide was teaming with gametocytes of plasmodium falciparum. In some RBC's ring forms of the parasites were seen. There were about 10-12 gametocytes/HPF. The RBC's were enlarged in size. There was no poikilvaytosis. Some target cells were also present. Urine analysis showed a dark coloured urine. Test showed Bilirubinuria and urobilinogen was markedly increased. Microscopically there were 20-25 RBC/HPF and 6-7 pus cells/HPF. The widal test was negative. Blood chemistry results were, serum Bilirubin, 4.2 mg/dl (mainly direct conjugated BILIRUBIN), ALT 70U/1, ALP 31.5 KA Units and Urea 150 mg/dl. The patient could not be screened for G-6PD as she expired on the second day.